Technical note: No increase in effective dose from half compared to full rotation pelvis cone beam CT. (2nd August 2017) - Hauri, Pascal; Hälg, Roger A.; Schneider, Uwe
Abstract: Purpose: To image the abdomen of a patient with a gantry mounted imaging system of a linear accelerator, different cone beam computed tomography (CBCT) protocols are available. The whole‐body dose of a full rotation abdomen CBCT and a half rotation CBCT was compared. In our clinic, both CBCT protocols are used in daily routine work. Methods: With an adult anthropomorphic Alderson phantom, the whole‐body dose per CBCT scan was measured with thermoluminescence dosimeters. The half rotation CBCT was applied such that the gantry mounted X‐ray source rotated around the right side of the phantom. The 183 measurement locations covered all ICRP recommended critical organs (except the gonads). The effective dose was calculated with the mean organ dose and the corresponding tissue weighting factors. A point‐by‐point dose comparison of both protocols was conducted. Results: The effective dose was 5.4 mSv ±5% and 5.0 mSv ±5% (estimated type B 1 σ ) for the full and the half rotation CBCT respectively. There was no significant difference ( α  = 0.05) in the effective dose within the precision of the measurement (1 σ  = 5%). The half rotation CBCT displayed an inhomogeneous dose distribution in a transversal phantom slice in contrast with the full rotation CBCT. In the imaging region, the mean dose was (20.5 ± 3.4) mGy and (19.2 ± 7.4) mGy (measured type A 1 σ ) for the full and the half rotation CBCT respectively. Conclusion: The half compared to the full rotation CBCT displays a smaller field‐of‐view in a transversal slice and no significant difference in the effective dose. Hence, the full rotation CBCT is favorable compared to the half rotation CBCT. However, by using the half rotation protocol, critical volumes in the patient can be spared compared to the full rotation protocol.